EFEK PENGGUNAAN SMARTPHONE BERKELANJUTAN DI MASA PANDEMI COVID 19 TERHADAP PERKEMBANGAN PSIKOLOGIS ANAK - Muhammad Sufyan As-Tsauri; Bambang Samsul Arifin; Tarsono Tarsono (Universitas Islam Malang, 2021)
The continuous use of smartphones during the Covid-19 pandemic has an impact on children's psychological development from emotional, social and moral aspects. This study also examines four important aspects, namely smartphone ownership, parental supervision, intensity of use, and the consequences of using the smartphone. This research is important to study as a result of the extension of the online learning period which has an impact on the increasing intensity of children using smartphones, so that the effects that arise can be taken into consideration for parents and teachers in monitoring children's growth and development. This research uses a qualitative approach to the type of case study. The data collection technique is done by interview, observation, and document study. The results showed that continuous smartphone use had a positive and negative impact on children's psychological development. The positive impact that arises is related to the social aspect, namely staying in touch with friends even during the Covid-19 pandemic. The negative impacts that arise, especially in children who use smartphones for more than 2 hours a day and without parental supervision, are related to emotional and social aspects of children such as children becoming lazy to learn, irritable, imitating behavior that is not giving up and using most of their time to play. online game.